Significant symptoms alleviation and tumor volume reduction after combined simultaneously integrated inner-escalated boost and volumetric-modulated arc radiotherapy in a patient with unresectable bulky hepatocellular carcinoma: A care-compliant case report. Issue 34 (August 2016) - Lin, Young-Hsiang; Hung, Shih-Kai; Chiou, Wen-Yen; Lee, Moon-Sing; Shen MD, Bing-Jie; Chen, Liang-Cheng; Liu, Dai-Wei; Tsai, Wei-Ta; Lin, Po-Hao; Shih, Yi-Ting; Hsu, Feng-Chun; Tsai, Shiang-Jiun; et al.
Abstract: Background: Clinically, elderly patients with unresectable bulky hepatocellular carcinoma (HCC) are difficult to manage, especially in those with co-infections of hepatitis B and C virus. Herein, we reported such a case treated with radiotherapy (RT) by using combined simultaneously integrated inner-escalated boost and volumetric-modulated arc radiotherapy (SIEB-VMAT). After RT, significant symptoms alleviation and durable tumor control were observed. Case Summary: At presentation, an 85-year-old male patient complained abdominal distention/pain, poor appetite, and swelling over bilateral lower limbs for 1 month. On physical examination, a jaundice pattern was noted. Laboratory studies showed impaired liver and renal function. Abdominal computed tomography (CT) revealed a 12.5-cm bulky tumor over the caudate lobe of the liver. Biopsy was done, and hepatocellular carcinoma (HCC) was reported histopathologically. As a result, AJCC stage IIIA (cT3aN0M0) and BCLC stage C were classified. Surgery, radiofrequency ablation (RFA), trans-catheter arterial chemoembolization (TACE), and sorafenib were not recommended because of his old age, central bulky tumor, and a bleeding tendency. Thus, RT with SIEB-VMAT technique was given alternatively. RT was delivered in 26 fractions, with dose gradience as follows: 39 Gy on the outer Plan Target Volume (PTV), 52 Gy in the middle PTV, and 57.2 Gy in the inner PTV. Unexpectedly, cyproheptadine (a newly recognized potential anti-HCC agent) was retrospectively found to be prescribed for alleviating skin itching and allergic rhinitis since the last 2 weeks of the RT course (2 mg by mouth Q12h for 24 months). After RT, significant symptoms alleviation and tumor volume reduction were observed for 32 months till multiple bone metastases. Before and after RT, a large tumor volume reduction rate of 88.7% was observed (from 608.4 c.c. to 68.7 c.c.). No severe treatment toxicity was noted during and after RT. The patient died due to aspiration pneumonia with septic shock at 4 months after bone metastases identified. Conclusions: SIEB-VMAT physically demonstrated double benefits of intratumor dose escalation and extra-tumor dose attenuation. Significant tumor regression and symptoms alleviation were observed in this elderly patient with unresectable bulky HCC. Further prospective randomized trials are encouraged to demarcate effective size of SIEB-VMAT with or without cyproheptadine.